PENGARUH LABELISASI HALAL, DOMPET DIGITAL, DAN GRATIS ONGKOS KIRIM TERHADAP KEPUTUSAN PEMBELIAN DARING MAKANAN IMPOR DI LOKAPASAR INDONESIA - Nadella, Aulia Ankin; Khasanah, Miftakhul (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
This research aims to determine the influence of halal labeling, affiliate marketing, consumer reviews, electronic wallets, and free shipping on purchasing decisions for imported food in the Indonesian marketplace. The research used a quantitative method with a total sample of 200 respondents. The sampling technique used in this study was purposive sampling, which is a technique using specific considerations in obtaining the sample. The sample criteria in this study included having an account in a marketplace application such as Tokopedia, Shopee, Lazada, Bukalapak, and JD.ID or Elevenia and having purchased imported food at the marketplace at least once. Collecting research data using a questionnaire and analyzing it with SmartPLS 3. The results of this study indicate that free shipping, affiliate marketing, and consumer reviews, have a positive and significant effect on the decision to purchase imported food in Indonesian marketplaces. Meanwhile, halal labeling and electronic wallets have no significant effect on purchasing decisions for imported food in Indonesian marketplaces.